Case study: Corticeira Amorim as the ambassador of Portugal’s country-brand - Pena, Patrícia Neto (2013)
Throughout the course of history, we have been watching the decline of borders physically and commercially; the opening of companies to the world market developed the possibility of expansion and an increase of business opportunities and competition. Nevertheless, globalization is not the only essential element of evolution, the development of technologies, allowed individuals to have access to information that for years was never available due to distance or difficult access. These factors are crucial pieces to brand architecture: brands have developed from only products in which communication was only a description of characteristics and benefits, to products that emphasise values and personality, that nowadays are translated by brand identity. Considering the enormous offer of brands, it becomes important to have an easy and distinctive identity in the market. The country of origin can be one of the attributes for brand identity that can contribute to a better definition of a brand in a world context. The country of origin is starting to be considered by brands in order to use them as brand leverage or even abolish any association to the country. Countries are also starting to develop their brands, aiming more than a perceived image by other countries, but also focusing on its economical impact, for example in exports. In this case study, we intend to focus on the impact of Portugal’s country brand on Corticeira Amorim, due to its important contribution to the Portuguese exports, and understand which benefits that can be achieved through the creation of partnerships.